A representação arquivística na tradição canadense: subsídios para elaboração de um modelo ideal de ensino por meio da semântica textual - MONTEIRO, Glenda da Rocha (2021)
It presents the contextual dynamics based on the postmodern and the drawn relationship between Linguistics and Archivology through semantics and Archival Representation, specifically in the activities of classification and description. Related to the research project "The Archival Representation: elements for the construction of an ideal teaching model through textual semantics from the Australian, Canadian and Brazilian contexts", is justified in the contribution to the construction of a theoretical and methodological framework about the Archival Representation in the Canadian context and for the creation of a teaching model based on methodological textual semantics and the criteria of textual construction of sense and constituent elements of the coherence and textual cohesion. Among the objectives are: the comparison of the different approaches in representation; to analyze how the archivists of the two institutions work on the construction of classification plans and research instruments; to analyze the research instruments of the two institutions, observing the linguistic analysis criteria established for this research. The method used to achieve these objectives is characterized by being an exploratory, theoretical and documentary study, having the semantic and textual construction criteria of meaning and constituent elements of textual coherence and cohesion as a methodology of analysis for understanding the paths of Archival Representation in the research tools of the Canadian Archives - Library and Archives Canada (LAC) and Provincial Archives of Manitoba. It addresses topics of Organization and representation of Archival Information; Linguistics and Semantics and presents as results an analysis of three research instruments of said Canadian institutions.